2002
DOI: 10.1063/1.1454212
|View full text |Cite
|
Sign up to set email alerts
|

Specific heat and thermal conductivity of BaTiO3 polycrystalline thin films

Abstract: The results of measurements by the ac heater-probe method of the specific heat and thermal conductivity of polycrystalline BaTiO3 films with thickness between 1 and 0.1 μm in a temperature range 120–440 K are presented. In the heating and cooling runs, the phase transition anomalies of the thermal properties in the region of each phase transition in the sequence of symmetry change m3m-4mm-mm2-3m have been observed. A temperature hysteresis is observed, which is the signature of the first order phase transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 9 publications
3
22
0
Order By: Relevance
“…[12][13][14] We show a consistent trend in the thermal conductivity of the BaTiO 3 films as a function of grain size, similar to what we have previously observed in nanograined SrTiO 3 films; we note that this consistency in the effects of nano-structuring on the thermal conductivity of BaTiO 3 does not appear among previous works. 15,16 Our data agree well with predictions for the grain boundary scattering effects on the thermal conductivity of BaTiO 3 using a simplified semi-classical model. The temperature trends suggest that phonon-boundary scattering events, both at grains and the film/substrate boundary, are the dominant source of thermal resistance.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…[12][13][14] We show a consistent trend in the thermal conductivity of the BaTiO 3 films as a function of grain size, similar to what we have previously observed in nanograined SrTiO 3 films; we note that this consistency in the effects of nano-structuring on the thermal conductivity of BaTiO 3 does not appear among previous works. 15,16 Our data agree well with predictions for the grain boundary scattering effects on the thermal conductivity of BaTiO 3 using a simplified semi-classical model. The temperature trends suggest that phonon-boundary scattering events, both at grains and the film/substrate boundary, are the dominant source of thermal resistance.…”
supporting
confidence: 76%
“…The current literature values regarding the effects of nano-structuring on BaTiO 3 range from studies with 150 nm grains exhibiting near-bulk thermal conductivities of 5.1 W m À1 K À1 (Ref. 16) to studies with grain sizes of 100 nm exhibiting thermal conductivities of 10.22 W m À1 K À1 , which is over twice that reported for the bulk thermal conductivity of BaTiO 3 . 18 See supplementary material for further discussion of these current discrepancies in the literature.…”
mentioning
confidence: 96%
“…I show a consistent trend in the thermal conductivity of the BaTiO 3 films as a function of grain size, similar to what Foley et al [94] has previously observed in nanograined SrTiO 3 films; this consistency in the effects of nano-structuring on the thermal conductivity of BaTiO 3 does not appear among previous works [268,269]. My data agree well with predictions for the grain boundary scattering effects on the thermal conductivity of Therefore, this work demonstrates the spectral nature of the thermal mean free paths of phonons in BaTiO 3 with typical length scales well beyond that predicted by a gray approximation using kinetic theory [270].…”
Section: Phonon Interactions With Grain Boundaries In Batiosupporting
confidence: 73%
“…Current literature values [269] regarding the effects of nano-structuring Jezowski et al [268] also found that for the ceramics with 30 nm grains the thermal conductivity was around 1.7 Wm −1 K −1 , which is lower than bulk and to be expected with nano-structuring.…”
Section: Literature Thermal Conductivity Of Batiomentioning
confidence: 99%
“…Such a small efficiency stems from the fact that the energy required to increase the temperature of the lattice is nearly always much larger than the energy required to destroy part of the polarization, thus releasing electric charges 2 . In our case of study the pyroelectric-engine efficiency is evaluated as where 19 . The temperature span is taken large enough so that the pumped transition heat as to have a constant temperature in isothermal processes, is neglegible 2,6,8 .…”
mentioning
confidence: 99%